2017
DOI: 10.1038/ncomms14444
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and constraint leading to complex multicellularity in the Ascomycota

Abstract: The advent of complex multicellularity (CM) was a pivotal event in the evolution of animals, plants and fungi. In the fungal Ascomycota, CM is based on hyphal filaments and arose in the Pezizomycotina. The genus Neolecta defines an enigma: phylogenetically placed in a related group containing mostly yeasts, Neolecta nevertheless possesses Pezizomycotina-like CM. Here we sequence the Neolecta irregularis genome and identify CM-associated functions by searching for genes conserved in Neolecta and the Pezizomycot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 88 publications
(138 reference statements)
8
118
0
1
Order By: Relevance
“…However, even among the Taphrinomycotina, which harbor mostly unicellular yeasts, species like Neolecta irregularis form ascocarps. Genome sequencing showed that Neolecta irregularis and Pezizomycotina share about 1,050 genes, not present in ascomycetous yeasts, with enriched functions related to complex multicellularity (334). Generally, five types of ascocarps are distinguished within the Pezizomycotina (apothecium, cleistothecium, gymnothecium, perithecium, or pseudothecium).…”
Section: Fruiting Body Formationmentioning
confidence: 99%
“…However, even among the Taphrinomycotina, which harbor mostly unicellular yeasts, species like Neolecta irregularis form ascocarps. Genome sequencing showed that Neolecta irregularis and Pezizomycotina share about 1,050 genes, not present in ascomycetous yeasts, with enriched functions related to complex multicellularity (334). Generally, five types of ascocarps are distinguished within the Pezizomycotina (apothecium, cleistothecium, gymnothecium, perithecium, or pseudothecium).…”
Section: Fruiting Body Formationmentioning
confidence: 99%
“…The data and approaches are only recently becoming available to support robust analyses to link genes to phenotypes. Some examples of successful applications of the approaches include the acquisition of enzymes needed for anaerobic growth by Saccharomyces [3133], gains of subtilase genes related to animal associated lifestyles [3436], genome reduction correlated to a yeast growth form [37,38], and changes in structure of centrioles for microtubule attachments [39]. …”
Section: Evolutionary Relationships Of Fungimentioning
confidence: 99%
“…The free living yeasts in the Ascomycota and the Cryptomycota parasite Rozella typically have genomes in the 7- to 12-Mb range [8084] and the Basidiomycota yeasts Cryptococcus are around 20 Mb [8486]. Lineages containing yeast-forming species tend to have smaller genomes (such as Schizosaccharomyces and Ashyba ), but this apparent reduction has occurred independently and multiple times in fungal history [37,38,87]. …”
Section: Evolution Of Genome Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Multicellular life has evolved independently at least 25 times, in groups as diverse as animals, fungi, plants, slime molds and seaweeds (Knoll, 2011;Nguyen et al, 2017;Niklas and Newman, 2013). All most complex living multicellular species, such as plants and animals, are descended from a single-celled ancestor, and understanding how these ancestors became multicellular remains a major challenge in the field of evolutionary biology.…”
Section: The Non-coding Genome and The Evolution Of Metazoan Multicelmentioning
confidence: 99%